The Basic Characteristics of the Pentraxin Family and Their Functions in Tumor Progression - Wang, Zeyu; Wang, Xing; Zou, Hecun; Dai, Ziyu; Feng, Songshan; Zhang, Mingyu; Xiao, Gelei; Liu, Zhixiong; Cheng, Quan (Frontiers in Immunology, 2020)
The pentraxin is a superfamily of proteins with the same domain known as the pentraxin domain at C-terminal. This family has two subgroups, namely; short pentraxins (C-reactive protein and serum amyloid P component) and long pentraxins (neuronal pentraxin 1, neuronal pentraxin 2, neuronal pentraxin receptor, pentraxin 3 and pentraxin 4). Each group shares a similar structure with the pentameric complexes arranged in a discoid shape. Previous studies revealed the functions of different pentraxin family members. Most of them are associated with human innate immunity. Inflammation has commonly been associated with tumor progression, implying that the pentraxin family might also participate in tumor progression. Therefore, we reviewed the basic characteristics and functions of the pentraxin family and their role in tumor progression.